In aid of community policy and framework development: A sustainable integrated community advancement program - ANA BELEN S. CUYUGAN; GINA E. AGUS; DANIEL D. DASIG JR.; MYRNA A. NIDEA; ELEONORA E. CLARICIA; MARY ANN B. TADUYO; EDMONGINO J. CAMACHO (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper describes the Sustainable Integrated Community Advancement Program, the University’s framework for social orientation and community involvement initiatives (SICAP). Community Development Programs, the Integrated Components of Extension Programs, Academic and Service Units, and the Commission on Higher Education, Philippines, all benefit from the framework’s comprehensive and oordinated approach to stakeholder engagement.Methodology: Using the Sequential Explanatory Method, which permits the collection and analysis of quantitative data to be followed by the collection and analysis of qualitative data, the researchers employed a mixed research methodology.Findings: The findings demonstrated that the programs had integrated the participants into national life and vitality and fostered participation, empowerment, and enhancement. By adopting and utilizing the proposed framework, the University was able to create and launch timely, appropriate, and effective programs.Implications/Novelty: The findings from this study will serve as the foundation for new policies, guidelines for their implementation, and a shift in the University’s priorities.